Bomba de calor ar/ar como sistema alternativo no aquecimento de aviários - Rodrigo Tessaro, Alcione (2011)
This research aimed to create two prototypes for general heating of aviary cutting the first prototype mounted from a heat pump air/air, and the second prototype mounted from passing an electric heater. As a specific objective to assess the energy performance of prototype 1 simulating various scenarios of temperature and air velocities of passage in its condenser, and compare this performance with the electrical efficiency of the prototype 2. The experiment was conducted at the Experimental Station of agro-meteorological State University of West of Paraná, Cascavel Campus, a Latitude 24º 59' South, Longitude 53º 26' West and altitude of 682 m in the period june-july 2011. From the data collected in prototypes 1 and 2 were calculated their coefficient of performance and energy efficiency. The survey results showed that the coefficient of performance heat pump prototype 1 ranged from 1.22 to 2.58 as a function of temperature of -3 to 30°C in its evaporator and varying the speed of air passing through your condenser. The best efficiency achieved by the prototype 2 was 0.96. Comparing the prototype, it was found that prototype 1 consumed 54% less electricity to produce the same amount of heat that the prototype 2, considering the same conditions of temperature and air velocity of passage. In relation to its applicability poultry, it was estimated that prototype 1 is able to meet the calorific requirement and temperature of a batch of up to 396 chicks in its initial phase, while the prototype 2 supply a maximum of up to 148 chicks. To this end, it was concluded that the prototype 1 in this work, assembled from a heat pump air/air, demonstrated technically be a new alternative system for heating of poultry cut because its technology employed is energy-efficient, also achieved the characteristics of zootechnical from temperature and air velocities required in an aviary of court.